2015
DOI: 10.1053/j.gastro.2014.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Foxl1-Cre–Labeled Hepatic Progenitor Cells and Their Descendants Impairs Recovery of Mice From Liver Injury

Abstract: BACKGROUND & AIMS Foxl1+ hepatic progenitor cells (HPCs) differentiate into cholangiocytes and hepatocytes following liver injury. We investigated the requirement for Foxl1+ HPCs in recovery from liver injury in mice. METHODS We developed mice in which we can trace and delete Foxl1-expressing HPCs and their descendants (Foxl1-Cre;RosaYFP/iDTR mice). Foxl1-Cre-negative mice were used as controls. Liver damage was induced in male mice by placing them on choline-deficient, ethionine-supplemented (CDE) diets for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 34 publications
5
95
0
Order By: Relevance
“…Excitingly, Hnf4α+/CK19+ cells have also been observed in a recent study demonstrating BEC‐derived hepatocytes during long‐term severe liver injury . Our results suggest that differentiation of BECs to hepatocytes is limited or impaired during ongoing injury and that a period of recovery is necessary to allow BEC differentiation to hepatocytes, as also shown elsewhere …”
Section: Discussionsupporting
confidence: 87%
“…Excitingly, Hnf4α+/CK19+ cells have also been observed in a recent study demonstrating BEC‐derived hepatocytes during long‐term severe liver injury . Our results suggest that differentiation of BECs to hepatocytes is limited or impaired during ongoing injury and that a period of recovery is necessary to allow BEC differentiation to hepatocytes, as also shown elsewhere …”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, Kordes et al observed that the proportion of cells engrafted following transplantation was dependent on the injury model used, suggesting that different progenitor sources drive regeneration in response to various types of injury, a theory consistent with other reports (7,18). If this is the case, it will be important to define the signals that activate each progenitor type in response to a specific injury.…”
supporting
confidence: 76%
“…When hepatocyte proliferation in the rat was blocked through administration of 2-acetylaminofluorene (AAF) followed by PHx, there was a massive expansion of oval cells from the periportal region into the parenchyma, and these cells were shown to give rise to hepatocytes (142, 143). Several studies in mice with YFP labeling of LPCs have reported that 2–30% of hepatocytes were YFP-positive after a CDE diet–induced liver injury (140, 141, 144), with no detection of YFP-positive hepatocytes from other forms of liver injury, such as PHx or chronic toxic injury from carbon tetrachloride (CCl 4 ) (140). However, several reports have indicated that LPCs do not contribute to liver regeneration.…”
Section: Cell Type–specific Roles Of Wnt/β-catenin Signaling In Livermentioning
confidence: 99%